CTD data Gerlache-Bismarck Strait (Antarctic Peninsula) during ECA56 expedition - Höfer, Juan; Mestre, Mireia; Hopwood, Mark James; Alarcon, Emilio; Vasquez, Valeska (PANGAEA, 2025)
CTD vertical profiles recorded using a SBE 25 plus CTD. The casts were taken on R/V Karpuj between the 9th and 16th of February 2020 in Gerlache-Bismarck Strait (Antarctic Peninsula) during the Chilean Antarctic Expedition #56 (ECA56). The research team was working on R/V Karpuj from INACH at the time under the supervision of Juan Höfer (chief scientist). The dataset includes temperature, conductivity, salinity, pressure, depth, chlorophyll a (Wet Labs) and oxygen concentration (SBE-43 oxygen meter). Raw CTD data were processed using SBE Data Processing Version 7.22.5 and SEAWATER Routines; and the dataset includes values averaged every 0.5 meters.
Keywords: Antarctica; Antarctic Peninsula; Bismarck Strait; CTD profiles; Gerlache Strait